Diversity of greenhouse gas emission drivers across European countries since the 2008 crisis. (21st October 2019) - Perrier, Quentin; Guivarch, Céline; Boucher, Olivier
ABSTRACT: In the context of climate change mitigation and the Paris Agreement, it is critical to monitor and understand the dynamics of greenhouse gas emissions over different regions of the world. In this study, we quantify the contributions of different drivers behind the observed emission decrease in Europe between 2009 and 2014. To this end, we build a novel dataset of deflated input–output tables for each of the 28 EU countries. This dataset enables us to conduct the first Structural Decomposition Analysis of emissions in European countries since the economic crisis. Our results show that the largest drivers of emissions have been the improvement in carbon intensity (−394 MtCO 2 e), largely offset by the economic recovery (+285 MtCO 2 e). However, other less intuitive drivers also played a significant role in the emission decline: changes in the production system (−104 MtCO 2 e), mostly driven by an increase in imports; the evolution of final demand patterns (−101 MtCO 2 e); a decrease in emissions due to household heating (−83 MtCO 2 e) and private transport (−24 MtCO 2 e), with a small offset from population growth (+39 MtCO 2 e). However, these aggregate figures mask significant variations between EU countries which we also document. This study highlights the importance of including changes in consumption patterns, trade and temperature anomalies in tracking and fostering progress towards the Paris Agreement goals. Key policy insights The largest drivers of EU greenhouse gas emissions changes between 2009 and 2014 have been improved carbon intensity and economic recovery. Changes in imports, production technologies, consumption patterns and household heating also played a significant role. Dynamics of change varied significantly from one country to another. Tracking these drivers is essential to monitor progress towards the Paris Agreement goals and increase ambition.